Improving self-efficacy with cognitive restructuring and self instruction: An experimental study in senior high school - Anggita, Thisadewi; Sugiyo, Sugiyo; Awalya, Awalya (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to analyze the effectiveness of cognitive behaviour therapy group counselling with cognitive restructuring techniques and effective self-instruction techniques to increase the self-efficacy of MA Al-Manar students. The population in this study were 136 students of MA AL Manar Semarang Regency, with a sample of 24 people consisting of 8 groups with cognitive restructuring techniques, 8 groups of self-instruction techniques, and 8 groups with cognitive restructuring techniques and self-instruction. . Data collection techniques using a psychological scale. The data analysis technique used Paired Sample t-Test and One-Way Anova test. The results showed that the intervention carried out with cognitive restructuring technique group counselling and self-instruction was effective to increase self-efficacy. These results imply the importance of guidance and counselling teachers to continue to develop the use of guidance and counselling services in dealing with student self-efficacy problems.